ANALISIS KEBIJAKAN INSENTIF PAJAK PPnBM MOBIL TERHADAP PENJUALAN MOBIL DI ERA PANDEMI COVID-19 - Riningsih, Duwi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The purpose of this research is for whether the economic growth policy through the Regulation of the Minister of Finance Number – 20/PMK.010/2021 PT. XXX which is one of the companies that sell cars in the Kediri City has an impact on car sales during the Covid-19 pandemic. The method used is descriptive analysis. The data obtained will be analyzed and processed according to the theory under that research to draw the conclusions. From the results of the study it can be concluded that PT. XXX car sales for certain classifications experienced the highest sales increase of up to 120% compared to the month before the 100% PPnBM reduction policy was implemented